Workstations for people with disabilities: an example of a virtual reality approach. Issue 3 (2nd July 2016) - Budziszewski, Paweł; Grabowski, Andrzej; Milanowicz, Marcin; Jankowski, Jarosław
Abstract : This article describes a method of adapting workstations for workers with motion disability using computer simulation and virtual reality (VR) techniques. A workstation for grinding spring faces was used as an example. It was adjusted for two people with a disabled right upper extremity. The study had two stages. In the first, a computer human model with a visualization of maximal arm reach and preferred workspace was used to develop a preliminary modification of a virtual workstation. In the second stage, an immersive VR environment was used to assess the virtual workstation and to add further modifications. All modifications were assessed by measuring the efficiency of work and the number of movements involved. The results of the study showed that a computer simulation could be used to determine whether a worker with a disability could access all important areas of a workstation and to propose necessary modifications.